2020
DOI: 10.1186/s40981-020-00371-2
|View full text |Cite
|
Sign up to set email alerts
|

Anesthetic management using a combination of anterior quadratus lumborum block and erector spinae plane block for robot-assisted partial nephrectomy: two case reports

Abstract: Background: There has been increasing attention regarding quadratus lumborum block (QLB) and erector spinae plane block (ESPB) as effective truncal blocks. There have been reports of combined QLB and ESPB usage in hip surgery resulting in a symbiotic increase in effectiveness. However, there have been no reports regarding robotassisted partial nephrectomy (RAPN), which requires multiple port holes ranging from near the xiphoid process to below the umbilicus. We hypothesized that the combined use of QLB and ESP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 22 publications
0
4
0
2
Order By: Relevance
“…There were multiple portholes starting at the xiphoid process and continuing to below the umbilicus, and the NRS score was 5 on movement 48 hours after surgery. 13 Our preliminary results showed that the PACU and the NRS scores from postoperative hours 1 to 24 were lower in the ESP block group than those in the non-ESP block group. Additionally, the total PCA consumption was significantly lower in the ESP block compared with the non-ESP block group.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…There were multiple portholes starting at the xiphoid process and continuing to below the umbilicus, and the NRS score was 5 on movement 48 hours after surgery. 13 Our preliminary results showed that the PACU and the NRS scores from postoperative hours 1 to 24 were lower in the ESP block group than those in the non-ESP block group. Additionally, the total PCA consumption was significantly lower in the ESP block compared with the non-ESP block group.…”
Section: Discussionmentioning
confidence: 61%
“…There were multiple portholes starting at the xiphoid process and continuing to below the umbilicus, and the NRS score was 5 on movement 48 hours after surgery. 13 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples include colorectal surgery, C-section, nephrolithotomy, nephrectomy, and gynecological procedures (46)(47)(48). It is also useful in robotic cases where multiple port sites are scattered over various quadrants (49). Because the QL block usually gets T12 -L1 branches, people have also used QL blocks for hip surgeries (50,51).…”
Section: Ultrasound-guided Quadratus Lumborum Block (Ql)mentioning
confidence: 99%
“…Mientras que los resultados de otro ensayo clínico reportan que, en pacientes sometidos a nefrectomía laparoscópica tradicional o asistida por robot, el bloqueo cuadrado lumbar bilateral disminuye el uso de opioides posoperatorios, además de prolongar el tiempo hasta la primera petición de opioides de rescate [23]. Concomitantemente, se ha propuesto sumar al bloqueo de cuadrado lumbar, el bloqueo del músculo erector de la espina, como una alternativa para mejorar la analgesia en el posoperatorio de la nefrectomía parcial asistida por robot; lo que ha demostrado ser útil en un reporte reciente de dos casos [24].…”
unclassified